Identifikasi Risiko Terjadinya Wanprestasi Terhadap Perjanjian Kartu Kredit yang Diajukan Secara Online di Bank Mega - Deviana Axfelia; Rasji Rasji (UNES Law Review, 2023)
This research was conducted to identify the risk of default in online credit card application agreements at Bank Mega. This research discusses the legal terms of an agreement, skill risks, the use of standard agreements, and the consequences of default. In addition, other risks such as personal financial conditions, lack of verification, high interest, irresponsible use, hidden fees, identity theft, and technical errors in online credit card applications are also explored. The results of this research underline the need for the socialization of laws governing online transactions so that people understand and comply with applicable regulations. Additionally, a solid understanding of the terms of the agreement and the risks involved in online transactions is essential to avoid future problems.